(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
A journey through my vision of the evolution of the theatre of objects from its beginnings at the end of the twentieth century to the present day. The visual arts and the “things”. Scenic bodies: object and actor. Thingness and carnality. The theatre of objects and its interaction with the visual, theatrical and multimedia arts. Research as an indissoluble part of the construction of the concept of object theatre. Training. Actuality of the object scene